Effect of mechanical activation on leaching of zinc and indium from indium-bearing zinc ferrite with sulphur dioxide as leachant and reductant. (3rd July 2021) - Fan, Yangyang; Liu, Yan; Niu, Liping; Jing, Tingle; Zhang, Ting-an
ABSTRACT: The indium-bearing zinc ferrite (IBZF) was synthesised, used as a research object, and mechanically activated with the planetary ball mill. Sulphur dioxide was introduced as reductant and leachant to create a reducing atmosphere and react with water to provide H + . The reductive leaching kinetics of activated IBZF samples was studied with sulphur dioxide as leachant and reductant. The results showed that the mechanical activation could change the physicochemical properties of IBZF significantly, thus improving its reactivity. The unreacted shrinking core model was an excellent fit for the kinetics of zinc and indium leaching. This indicated that the leaching process was controlled by surface chemical reaction and the activation energy was 62.57 and 57.30 kJ·mol −1 . After the mechanical activation for 60 min, the activation energies of zinc and indium leaching decreased to 40.66 and 44.26 kJ·mol −1, respectively. In addition, the reaction order for the partial pressure of sulphur dioxide for zinc and indium leaching decreased from 1.28 to 1.25 and from 1.30 to 1.28, respectively.